2002
DOI: 10.1007/s00210-002-0553-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prodelphinidins isolated from Ribes nigrum on chondrocyte metabolism and COX activity

Abstract: Articular diseases, such as osteoarthritis, is the clinical expression of the loss of cartilage function. COX inhibitors are widely used in the treatment of such pathologies for their beneficial effects on inflammation but often produce a negative activity on cartilage synthesis. In this study, we determined the effect of different prodelphinidins, the major compounds isolated from Ribes nigrum leaves, on the proteoglycans (PGs), type II collagen (coll. II) and prostaglandin E(2) (PGE(2)) production by differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 46 publications
0
35
0
1
Order By: Relevance
“…The subject of the present study is extracts from leaves of blackcurrant, strawberry and apple, which exhibit a series of positive actions with respect to biological systems. Extracts from currant leaves, aside from phenolic compounds that mainly belong to quercetin and kaempferol derivatives [2,3], also contain large amounts of prodelphinidins, and can thus be used for treating osteoarthritis [4]. Declume [5] showed that a water-alcohol extract from currant leaves has an antiinflammatory effect, and the tannins it contains are a competitive inhibitor of cAK with respect to both ATP and synthetic peptide substrate [6].…”
Section: Introductionmentioning
confidence: 99%
“…The subject of the present study is extracts from leaves of blackcurrant, strawberry and apple, which exhibit a series of positive actions with respect to biological systems. Extracts from currant leaves, aside from phenolic compounds that mainly belong to quercetin and kaempferol derivatives [2,3], also contain large amounts of prodelphinidins, and can thus be used for treating osteoarthritis [4]. Declume [5] showed that a water-alcohol extract from currant leaves has an antiinflammatory effect, and the tannins it contains are a competitive inhibitor of cAK with respect to both ATP and synthetic peptide substrate [6].…”
Section: Introductionmentioning
confidence: 99%
“…In human chondrocytes, prodelphinidin increased the synthesis of cartilage matrix major proteins, PGs and type II collagen, and inhibited PGE 2 synthesis by down-regulating COX-2 action [91]. These in vitro studies have provided support for additional preclinical assessment of prodelphinidin in the treatment of OA.…”
Section: Pomegranatementioning
confidence: 96%
“…Pomegranate demonstrated anti-inflammatory action via inhibiting the activity of the major inflammatory enzyme (COX-2) and the production of its inflammatory mediator product PGE 2 [90]. Pomegranate extracts also prevented the activation of molecules [MAPK kinase-3 (MKK-3), p38-MAPK] which are the molecules of the stimulatory pathway for inducing OA in chondrocytes [91].…”
Section: Pomegranatementioning
confidence: 99%
“…The same lyophilizate exhibited potent analgesic activity in the acetic acid-induced writhing test after single dose intraperitoneal administration to mice . Garbacki et al (2002) tested proanthocyanidins isolated from R. nigrum leaves to evaluate their chondroprotective potential and their COX inhibition properties using human cartilage, purified COX-1 and COX-2 enzymes and a COX whole blood assay. The compounds stimulated type II collagen production and inhibited purified COX with a certain selectivity against COX-2, but they had no effect on COX in the whole blood assay.…”
Section: Blackcurrant Leavesmentioning
confidence: 99%